IFRS : a quick reference guide - Kirk, R. J. (Robert J.), 1951-; ScienceDirect eBooks (Amsterdam ; Boston ; London : CIMA, 2009)
This book is all about how companies are applying the key principles in International Financial Reporting Standards (IFRS) and shows this by use of extensive examples of UK company accounts. The book provides coverage of the key points of each standard and links that with actual practice. It is not a detailed guidance book as such, or a transistion book from UK standards to IFRS, but a quick reference for the busy accountant which shows how to apply the key points of each standard by reference to how other companies have done it.
Introduction; The Regulatory Framework and Presentation of Financial Statements; Asset Valuation: Non Current Assets; Asset Valuation: Intangible Assets; Asset Valuation: Inventories and Construction Contracts Liabilities; Performance Measurement; Employee Costs; Foreign Trading; Cash Flow Statements; Disclosure Standards; Group Accounting; Financial Instruments; Sundry Financial Reporting Standards.
Includes index.
Print version record.
Elsevier
Keywords: Financial statements; Financial statements -- Standards -- Great Britain; Financial statements; Financial statements -- Standards; Great Britain; Electronic books